Upaya Meningkatkan Kemampuan Berpikir Kritis Peserta Didik Kelas X SMAN 1 Rengel Kabupaten Tuban pada Materi Proses Masuknya Hindu-Buddha ke Nusantara melalui Model Pembelajaran Problem Based Learning (PBL) - Rangga Bachtiar Mas; Nasution Nasution; Zeni Sofia Familawati (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2023)
Low level of critical thinking among the dozens of students working on question-based cognitive critical thinking tests in History subjects. The purpose of this research was to demonstrate efforts to improve learners' critical thinking skills in history learning through a problem-based learning model in class X of Public Senior High School 1 Rengel, Tuban Regency. The results showed that the problem-based learning (PBL) learning model in class X of Public Senior High School 1 Rengel, Tuban Regency could increase learners’ critical thinking skills from the results of the tests given according to the minimum completeness criteria. The conclusion of this research is that the problem-based learning (PBL) learning model is effective in increasing the critical thinking skills of class X learners of Public Senior High School 1 Rengel, Tuban Regency in History subject.